Cheilolejeunea vittata (Steph. ex G. Hoffm.) R.M. Schust. & Kachroo (Lejeuneaceae: Marchantiophyta) A newly recorded species from India (Bangladesh Journal of Plant Taxonomy, 2016)
Cheilolejeunea vittata (Steph. ex G. Hoffm.) R.M. Schust. & Kachroo is reported and described for the first time in Indian bryoflora from Manipur.Bangladesh J. Plant Taxon. 23(2): 209-213, 2016 (December)